A novel methodology for the design and optimisation of oil and gas offshore platforms. (15th October 2019) - Nguyen, Tuong-Van; Barbosa, Yuri M.; da Silva, Julio A.M.; de Oliveira Junior, Silvio
Abstract: Oil and gas offshore platforms present similar structural designs and include operations such as separation, compression and pumping. However, they handle large variations in the production of hydrocarbons and water over time. They may also follow different modes of operation depending on the field characteristics and fluid properties. It is therefore not possible to suggest a standard layout of an offshore platform that can be widely implemented in distinct petroleum regions. The oil and gas processing plant should be designed adequately to maximise the hydrocarbon production and minimise the power, heating and cooling demands. The utility plant should be designed appropriately to minimise the fuel consumption and cover the energy needs in all production phases. The present paper presents a generic methodology that addresses these challenges and builds on a combination of process simulation, energy analysis and optimisation routines. Possible platform layouts are sized, evaluated and ranked, based on preliminary estimates of the production profiles and petroleum properties. This methodology is applied to three case studies, derived from actual field data from Norway and Brazil, with different field conditions, fluid compositions (e.g. negligible, medium and high CO2 contents of the well-fluids) and operational requirements (e.g. gas export, injection and lift). The results illustrate the benefits of the proposed methodology, as a comparison with the 'business-as-usual' case shows up to 25–30% energy savings and CO2 -emissions along the field lifespan. Highlights: A novel methodology for designing and optimising energy-efficient platforms is presented. Different petroleum compositions and production profiles are considered. Various concepts for local power and heat generation and process design are assessed. Energy savings and CO2-reductions can reach up to 25–30% compared to business as usual scenarios.